Proceedings of the 7th International ACM SIGACCESS Conference on Computers and Accessibility 2005
DOI: 10.1145/1090785.1090792
|View full text |Cite
|
Sign up to set email alerts
|

Programmer-focused website accessibility evaluations

Abstract: Suggested methods for conducting website accessibility evaluations have typically focused on the needs of end-users who have disabilities. However, programmers, not people with disabilities, are the end-users of evaluations reports generated by accessibility specialists. Programmers' capacity and resource needs are seldom met by the voluminous reports and long lists of individual website fixes commonly produced using earlier methods. The rationale for the need to consider the whole website development process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
(8 reference statements)
0
18
0
1
Order By: Relevance
“…However, it seems that there is a disconnect between what people believe and do, similar to what Lazar et al (2004) found: webmasters are aware of Downloaded by [University of Arizona] at 06:21 05 February 2015 web accessibility practices, while the evidence supports that the web is non-accessible. The fact that conformance badges are displayed on non-conformant websites (Gilbertson and Machin 2012) may indicate an overreliance on tools and might be a symptom of communication problems between the HCI specialist and programmers (Law et al 2005). This means that if one is educated in web accessibility, it should be strongly emphasised that using only automated tools to assess accessibility might not be enough to identify all the accessibility problems in a web page.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…However, it seems that there is a disconnect between what people believe and do, similar to what Lazar et al (2004) found: webmasters are aware of Downloaded by [University of Arizona] at 06:21 05 February 2015 web accessibility practices, while the evidence supports that the web is non-accessible. The fact that conformance badges are displayed on non-conformant websites (Gilbertson and Machin 2012) may indicate an overreliance on tools and might be a symptom of communication problems between the HCI specialist and programmers (Law et al 2005). This means that if one is educated in web accessibility, it should be strongly emphasised that using only automated tools to assess accessibility might not be enough to identify all the accessibility problems in a web page.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In another example, Law et al [12] have developed a method for reporting the results of website accessibility evaluations that modifies suggested processes (e.g., [29]) to make it programmer-centric. The automated accessibility evaluation tools of the time produced voluminous stacks of paper, which essentially were lists detailing where in the code and on what pages of the site the violations occurred [12].…”
Section: Developer-centric Methods In Udmentioning
confidence: 99%
“…The automated accessibility evaluation tools of the time produced voluminous stacks of paper, which essentially were lists detailing where in the code and on what pages of the site the violations occurred [12]. These lists were often appended to lengthy evaluation reports and handed to programmers with the expectation that all they had to do was fix everything in the report.…”
Section: Developer-centric Methods In Udmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, it is important to evaluate accessibility as close as possible to what is delivered to the user [2]. The drawback of this Web site evaluation procedure is the possibility of guiding to misleading accessibility results, for the point of view of the developer [3] or of the team manager that tries to assess the effort of repairing a web site. For example, if a template intrinsically contains an accessibility problem, that problem is reported as often as the template is used within the page/site.…”
Section: Introductionmentioning
confidence: 99%